Structural Characterization of Prosopis africana Populations (Guill., Perrott., and Rich.) Taub in Benin - Towanou Houètchégnon; Dossou Seblodo Judes Charlemagne Gbèmavo; Christine Ajokè Ifètayo Nougbodé Ouinsavi; Nestor Sokpon (International Journal of Forestry Research)
The structural characterization of Prosopis africana of Benin was studied on the basis of forest inventory conducted in three different vegetation types (savannah, fallow, and field) and three climate zones. The data collected in 139 plots of 1000 m2 each related to the diameter at breast (1.3 m above ground), total height, identification, and measurement of DBH related P. africana species height. Tree-ring parameters such as Blackman and Green indices, basal area, average diameter, height of Lorey, and density were calculated and interpreted. Dendrometric settings of vegetation type and climate zone (Guinea, Sudan-Guinea, and Sudan) were compared through analysis of variance (ANOVA). There is a significant difference in dendrometric settings according to the type of vegetation and climate zone. Basal area, density, and average diameter are, respectively, 4.47 m2/ha, 34.95 stems/ha, and 37.02 cm in the fields; 3.01 m2/ha, 34.74 stems/ha, and 33.66 cm in fallows; 3.31 m2/ha, 52.39 stems/ha, and 29.61 cm in the savannahs. The diameter distribution and height observed at the theoretical Weibull distribution show that the diameter and height of the populations of the species are present in all positively skewed distributions or asymmetric left, a characteristic of single-species stands with predominance of young individuals or small diameters or heights.